The influence of rice paper on the texture characteristics of modern Chinese boneless paintings / Feifei Duan, Issarezal Ismail and Ishak Ramli - Duan, Feifei; Ismail, Issarezal; Ramli, Ishak (Universiti Teknologi MARA, Perak, 2024)
To analyse and summarise the textural features of contemporary Chinese boneless painting, this essay focuses on the application of modern Chinese boneless painting techniques on rice paper. On raw, cooked, and half-cooked rice papers, we experimented with Chinese contemporary boneless painting techniques in this study to produce a range of modern boneless painting texture samples. The texture and visual effects offered are significantly distinct yet rice paper with different qualities is expressed using the same contemporary Chinese boneless painting methods. It so displays how the paper used in the creation of modern Chinese boneless paintings has an impact on their artistic manner. This sort of research, which summarises the technical features of current Chinese boneless paintings from the standpoint of painting media, is very important to the advancement and innovation of contemporary Chinese boneless paintings. The adoption of contemporary Chinese boneless painting methods can also aid more painters.